Diabetes: A Risk Factor for Catheter-Associated Infections. (1st January 2015) - Bomberg, Hagen; Kubulus, Christine; List, Franka; Albert, Noemi; Schmitt, Kathrin; Gräber, Stefan; Kessler, Paul; Steinfeldt, Thorsten; Standl, Thomas; Gottschalk, André; Wirtz, Stefan P.; Burgard, Gerald; et al.
Abstract : Background and Objectives: The incidence of infectious complications associated with continuous regional anesthesia techniques is a matter of concern. Our objective was to determine whether patients suffering from diabetes are at an increased risk of catheter-related infectious complications. Methods: The German Network for Regional Anaesthesia database was analyzed between 2007 and 2012. After proof of plausibility, data of 36, 881 patients undergoing continuous regional anesthesia were grouped in I: no diabetes (n = 32, 891) and II: any diabetes (n = 3990). The analysis focused on catheter-related infections after strict definition. Differences among the groups were tested with t and χ 2 tests. Odds ratios were calculated with logistic regression and adjusted for potential confounders. Results: Patients with a diagnosis of diabetes had an increased incidence of catheter-related infections (no diabetes 3.0% vs any diabetes 4.2%; P < 0.001). Among all patients, diabetes remained an independent risk factor for infections for all sites after the adjustment for potential confounders (odds ratio [OR] = 1.26; 95% confidence interval [95% CI], 1.02–1.55; P = 0.036). The risk of infection was significantly increased in peripheral catheters only in the lower limb (adjusted OR = 2.42; 95% CI, 1.05–5.57; P = 0.039). If neuraxial catheters were used, the risk was significantly increased only in lumbar epidural (adjusted OR = 2.09; 95% CI, 1.18–3.73; P = 0.012) for diabetic patients compared with nondiabetic patients. Conclusions: The presence of diabetes is associated with an increased risk for catheter-related infections in lower limb and lumbar epidural. Specific care should be taken to avoid and detect infections in this population.